Modifications to structural, techno-functional and rheological properties of sesame protein isolate by high pressure homogenization - Baskıncı, Tuğba; Gul, Osman (Elsevier BV, 2023)
In this study, we aimed to determine the effect of high pressure homogenization (HPH) at a pressure up to 150 MPa on microstructural, techno-functional and rheological properties of sesame protein isolate (SPI). HPH treatment caused a partial change in the secondary structure of SPI, however, the changes in surface hydrophobicity and free -SH groups, indicating HPH had significant effect on the tertiary structure. After the HPH treatment, the particles dispersed homogeneously with more rougher surface. Sesame proteins had the smallest particle size (0.79 μm) and highest zeta potential (38.83 mV) at 100 MPa pressure. The most developed water/oil holding capacity, emulsification and foaming properties were achieved at 100 MPa pressure. However, the maximum stable foam formation (83.33 %) was determined at 150 MPa pressure. When the shear rate is fixed as 50 1/s, an increase in the viscosity value of the samples treated with 100 and 150 MPa pressure was detected compared to the control sample, while the lowest viscosity was determined the ones treated at 50 MPa. In all samples except 50 MPa pressure-treated proteins, viscoelastic character became dominant with increasing frequency (G' > G″). Modification with HPH resulted in a decrease of about 15 °C in the gelation temperature of SPI.